Synthetic pheromonefor mating disruption o/Cydia molesta (Busck) (Lepidoptera Tortricidae) and preliminary trials on Anarsia lineatella Zell. (Lepidoptera Gelechiidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Experiences on mating disruption of OFM (Cydia molesta) and PTB (Anarsia lineatella) with synthetic female pheromone in peach orchards of Emilia Romagna (Northern Italy) are reported. Tue trials were carried out on a plot of 1.3 ha in 1987, while in 1988 5 plots fora total area of 10 ha were involved. 500 dispensers/ha were allocated; the release rate was more than 50 mg/ha/h fora period of 6 months with the OFM Iure, while the attractant for PTB, applied only in 1988, was completely exhausted in three months time. The fruit damage was generally less than 1 %; only in two plots, with late ripening cultivar, a higher damage was noticed (max 7.6%). High population density and tall trees were the main causes of poor control.
Keywords: peach; Cydia molesta; Anarsia lineatella; pheromones; mating disruption